A review on the novel Heterocyclic Antileishmanial drugs for the treatment of Leishmaniasis - Ibnat, Adeeba (Brac University, 2020)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2019.